Ischaemia reperfusion injury in liver transplantation: Cellular and molecular mechanisms - Dar, Wasim A.; Sullivan, Elise; Bynon, John S.; Eltzschig, Holger; Ju, Cynthia (Liver international, 2019)
Liver disease causing end organ failure is a growing cause of mortality. In most cases, the only therapy is liver transplantation. However, liver transplantation is a complex undertaking and its success is dependent on a number of factors. In particular, liver transplantation is subject to the risks of ischaemia‐reperfusion injury (IRI). Liver IRI has significant effects on the function of a liver after transplantation. The cellular and molecular mechanisms governing IRI in liver transplantation are numerous. They involve multiple cells types such as liver sinusoidal endothelial cells, hepatocytes, Kupffer cells, neutrophils and platelets acting via an interconnected network of molecular pathways such as activation of toll‐like receptor signalling, alterations in micro‐RNA expression, production of ROS, regulation of autophagy and activation of hypoxia‐inducible factors. Interestingly, the cellular and molecular events in liver IRI can be correlated with clinical risk factors for IRI in liver transplantation such as donor organ steatosis, ischaemic times, donor age, and donor and recipient coagulopathy. Thus, understanding the relationship of the clinical risk factors for liver IRI to the cellular and molecular mechanisms that govern it is critical to higher levels of success after liver transplantation. This in turn will help in the discovery of therapeutics for IRI in liver transplantation – a process that will lead to improved outcomes for patients suffering from end‐stage liver disease.